Software Engineering Practices in the development of applications for Smart Cities: An Experience Report of Teaching in a Contemporary Context - Viana, Davi; Rosa, Thatiane de Oliveira; Silva, Francisco; Durans, Pablo; Aragão, Alexandre; Kon, Fabio; Goldman, Alfredo (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
The heterogeneity of contemporary systems has turned the Software Engineering (SE) area even more challenging, since it is necessary to identify practices that are more adequate according to the technologies and context. Thus, practitioners need to be better prepared for these new systems. The area of Smart Cities (SC) is emerging and presents new challenges in conceptual, technical and academical degrees. This paper presents an experience report of SE practices in the development of SC applications. Five teams used the SC platform and developed their projects, creating software documentation, while applying agile practices. As a result, we identified that some UML diagrams were not adequate to model specific SC's aspects and microservices. Furthermore, we identified that there was a low application of the proposed agile practices, such as pair programming and daily meetings. Despite being the first time this class was taught, we identified gaps that need to be investigated in order to identify which SE practices are more adequate for such context.